Donation of the body and its parts in the construction of parenthood - Alfano, Linda; Fontana, Paolo; Lorettu, Liliana; Ciliberti, Rosagemma (Acta Biomedica Atenei Parmensis, 2023)
The developments of science and technology make possible today unprecedented exchanges of body parts by multiplying the figures and links that intervene in the process of building parenthood and generating significant ethical and judicial controversies. Body donation in the procreative field constitutes an anthropological and social phenomenon of increasing attention, which contributes to one of the most intimate and profound aspirations of the human being and which requires a careful evaluation of the various interests involved and a thorough reflection on the statute and characteristics of the parental bond. The interest of the child, the dignity of women and the quality of human relations are the parameters of this analysis and, at the same time, the perimeter of the judgment. However, the approach to these issues is complicated not only by the extreme heterogeneity of legislation but also by suspicions and prejudices that hinder reflection appropriate to the complexity of the issues involved. Investigate the reasons for the choice of donation, the criticalities, and possible drifts, without closing in their subjective value horizon, is an unavoidable prerequisite for a comparison with the new social realities of the family that respects the fundamental rights of the person.